Affordability And Subsidies In Public Urban Transport : What Do We Mean, What Can Be Done? - Estupinan, Nicolas (The World Bank, 2008)
Subsidy policies on public urban transport have been adopted ubiquitously. In both developed and developing countries, subsidies are implemented to make transport more affordable. Despite their widespread implementation, there are virtually no quantitative assessments of their distributional incidence, making it impossible to determine if these instruments are pro-poor. This paper reviews the arguments used to justify subsidy policies in public urban transport. Using different tools to quantitatively evaluate the incidence and distributive impacts of subsidy policy options, the paper analyzes the findings of a series of research papers that study urban public transport subsidy policies in developed and developing countries. The available evidence indicates that current public urban transport subsidy policies do not make the poorest better off. Supply-side subsidies are, for the most part, neutral or regressive; while demand-side subsidies perform better-although many of them do not improve income distribution. Considering that the policy objective is to improve the welfare of the poorest, it is imperative to move away from supply-side subsidies towards demand-side subsidies and to integrate transport social concerns into wider poverty alleviation efforts, which include the possibility of channeling subsidies through monetary transfer systems or through other transfer instruments (food subsidies, health services and education for the poor). The general conclusion of the paper is that more effort should be devoted to improve the targeting properties of public urban transport subsidies using means-testing procedures to ensure a more pro-poor incidence of subsidies